Adulteration of Raw Milk in Selected Regions of Tangail District of Bangladesh - Bari, L; Hoque, MR; Reza, MSA; Hossain, MA; Islam, A (Journal of Environmental Science and Natural Resources, 2015)
At the present time adulteration of food especially raw milk is becoming a burning issue. Normally milk is adulterated with water, starch, skim milk powder, sugar, detergent, and fat, recently formalin also added with milk to increase the shelf life of milk. Thats why it is very essential to detect the prevalence of adulteration of milk. The present experiment was conducted to know the adulteration of milk. Total thirty milk samples were collected from five different bazaars (Tangail town, Santosh Bazaar, Porabari Bazaar, Boilla Bazaar, Bajitpur Bazaar) of Tangail district where six samples were taken from each entry point. The mean Specific gravity was 1.021, 1.020, 1.019, 1.019 and 1.020 respectively which were lower than standard 1.032 (BSTI, 2000). The results clearly suggest that water was the most common adulterant in almost all sample of raw milk collected. 56.67% and 50% samples were adulterated with starch and skim milk powder respectively. Two types of preservatives namely borax and sodium bicarbonate were detected in the fluid milk from the study areas. Out of all samples, 23.33% was adulterated with sodium bicarbonate and 16.66% with borax. However, none of the samples contained either formalin or hydrogen peroxide. It could therefore be inferred that, the consumers need to be more cautious regarding the quality of raw milk. J. Environ. Sci. & Natural Resources, 8(1): 41-44 2015